A LITERAL SYNTHESIS ALGORITHM FOR HIGH PROCESS REGULATION IN ICOFLS (International Journal of Engineering and Computer Science, 2013)
This paper presents an implementation algorithm for Intelligent Changeover Fuzzy Logic Switching System (ICOFLS) for domestic load management. The algorithm achieves high quality regulation through utilization of fuzzy logic controller in self-managing the three entities viz: Phase lines, Generator system and Inverter system. The MATLAB Simulink fuzzy logic blockset was used in this research for high process regulation. With mamdani fuzzy inference structure for the system algorithm developed, the fuzzy plots were generated for ICOFLS. In this context, this paper proposes a fuzzy logic control (FLC) Altera Stratix IV GX FPGA which has been designed and fabricated with 0.8μm CMOS technology for process real-time control for the ICOFLS. The high regulation factor, simplicity, flexibility and adaptability of FLC FPGA makes ICOFLS dual knowledge based viz: inference control rules implement and output scale regulation. The synthesis algorithm and experimental results of ICOFLS model show that the system demonstratesresilence, stability, cost effectiveness and environmental sustainability.